Kajian Penentuan Komoditas Unggulan Penunjang Food Estate di Kabupaten Malang: Komoditas Unggulan Penunjang Food Estate - Subagyo, Widiyanto Hari (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2023)
Food Estate is the development of the concept of food production in an integratedmanner through the activities of the food crops, horticulture, plantation andlivestock sub-sectors. The need for a priority scale of economic sectors in MalangRegency as a leading commodity to support food estate. So a research wasconducted with the aim of determining the leading sub-sectors and determiningthe leading commodities in the food estate supporting sector in Malang Regency.The type of research used is combined research or qualitative and quantitativecombined research. With a spatial approach, Economic Approach, EcologicalApproach, and Resource Management Approach. The analysis method used is theLeading Commodity Analysis, Location Quotient (LQ), Shift Share, Growth Share.The results showed that 6 sub-sectors became the basis sector, 5 sub-sectorswith a progressive sector typology, and 9 sub-sectors with a fast-growingnational typology. There are 4 main commodities in Malang Regency, namely RedOnion, Cayenne Pepper, Cabbage and Tomato. These four superior commoditiescan support the Food Estate in Malang Regency